Impact of human activities on the spatio-seasonal dynamics of plankton diversity in drained marshes and consequences on eutrophication. (1st March 2020) - David, Valérie; Tortajada, Sébastien; Savoye, Nicolas; Breret, Martine; Lachaussée, Nicolas; Philippine, Olivier; Robin, François-Xavier; Dupuy, Christine
Abstract: The functional diversity of two planktonic functional compartments, the nano-microphytoplankton and the mesozooplankton was used in order to better understand i) the drained marshes functioning and their related ecological functions, ii) the impacts of human control (replenishment) and human activities on the catchment basin (urbanization and catchment basin size). It was based on a monthly seasonal survey on 7 freshwater drained marshes. Both nano-microphyto- and mesozooplankton displayed high seasonal variations linked to the environmental fluctuations and human control on sea lock gates. Winter presented the lower biomasses of both compartments. Winter that is characterized by low water temperature, low light availability and high flood is actually related to the dominance of tychopelagic phytoplankton and K-strategists zooplankton. Spring and summer were characterized by i) the succession of pelagic large cells, small cells and then taxa with alternatives food strategies due to nitrogen limitation and phosphorous desorption from the sediment leading to eutrophication processes and ii) the dominance of r-strategists for mesozooplankton. The artificial summer replenishment acts positively on water quality by decreasing the eutrophication processes since the nitrogen inputs limit the proliferation of phytoplankton mixotrophs and diazotrophs and increase the ecological efficiency during the warm period. Both small and large catchment basins may lead to summer eutrophication processes in drained marshes since the largest ones imply higher hydrodynamic features at the root of large inputs of nitrogen nutrient favoring the phytoplankton development while the smallest ones exhibit hypoxia problems due to high proliferation of macrophytes. Urbanized marshes are less subjected to eutrophication during summer than non urbanized marshes due to more recurrent nutrient inputs from urban waste. However they exhibited a lower ecological efficiency. The results suggest that a better management of the hydrodynamics of such anthropogenic systems can avoid eutrophication risks on coastal areas. Graphical abstract: Image 1 Highlights: Polder areas needs a better hnowledge of how human impacts act on them. A functional diversity approach of two planktonic functional compartments. The artificial summer replenishment decreased the eutrophication processes. The catchment basins size may lead to summer eutrophication via several processes. Urbanized marshes are less subjected to eutrophication during summer.